Varieties of Religious Environmentalism: Understanding the Theological Foundations of Environmental Concern among Christians and Muslims in Northeast Nigeria - Shehu, Muazu (The international journal of religion and spirituality in society, 2017)
Current research on the connection between religion and the environment indicates that religious beliefs may provide a form of motivation for environmental stewardship and serve to rationalize environmental activism. This study used data from the profoundly religious region of northeast Nigeria to explore the various ways in which religious ideas inform pro-environmental action and to investigate whether motives for pro-environmental action differ between Christians and Muslims in the region. The study used both qualitative analysis of interviews with leaders of some selected congregations and statistical analysis of questionnaire data collected from members of those congregations to achieve these objectives. Overall, there is strong evidence that religious values contribute to three broad motives for pro-environmental action—namely, ecocentrism, anthropocentrism, and theocentrism. Although the study did not find significant variations in the religious motives for pro-environmental action among the two groups, some differences have been observed in the concepts used by the groups to explain their motives for environmental stewardship. The implications of these findings for researching religious environmentalism and environmental reform policy in religiously conservative societies are discussed.